Studying performance evaluation of hybrid e-bike using solar photovoltaic system - Safwan A. Hamoodi; Ahmed A. Abdullah Al-Karakchi; Ali N. Hamoodi (Bulletin of Electrical Engineering and Informatics, 2022)
Hybrid e-bike system is a bicycle included electric hub motor used to aid propulsion. A solar package with main components is built with it. This study included the travelled distance divided by time under only the batteries and batteries with photovoltaic (PV) modules (at different hours during the day). A comparison between two methods is made and documented in this paper. The paper aims to captivate the fettle and experiences with the use of e-bike. Commuting distance per hour was approximately 6.8 km/h. The current limitations must not exceed (10.4 A) and the big challenge, no shading plops on solar panels due to rider. Finally, depending on the solar irradiance with time curve, hybrid e-bike gave longer travelled distance with respect to time as compared with the batteries case study.